PENGARUH PGPR AKAR BAMBU APUS DAN PUPUK LIMBAH CAIR NANAS TERHADAP PERTUMBUHAN BAWANG DAUN UNTUK INFORMASI MASYARAKAT - Yulistiana, Elza -; widowati, Hening; sutanto, *Agus (Universitas Muhammadiyah Metro, 2020)
Increasing agricultural crop production, especially onion, can be done by improving the optimal growing environment for plants. Plant roots can be optimized for the absorption of nutrients and water in the process of photosynthesis. One way that can be used is by applying Plant Growth Promoting Rhizobacteria (PGPR). In addition to increasing the content of micro and macro elements in the soil can also support the growth of leek plants obtained by applying Pineapple Liquid Waste (LCN) made using bacterial isolation and can meet the needs of nutrients in plants. This study aims to determine the effect Plant Growth Promoting Rhizobacteria (PGPR) from Apus (Gigantochola apus) bamboo root and Pineapple Liquid Waste (LCN) fertilizer on the growth of leeks (Allium fistulosum L.), then the results of this study are treated as community information in the form of Leaflets. The method used in this study was an experiment using a Completely Randomized Design (CRD) system consisting of 4x4 factorials with 3 replications. Based on the results of calculations and data analysis, the results show that there is an effect of PGPR and LCN on the growth of scallions on the height and number of tillers per scallion plant family, but there is no influence on pseudo stem circumference and wet weight per scallion plant family, and the results of this study can be used as a source of public information in the form of leaflets with an average percentage included in good eligibility criteria.